(untitled) (Research, Society and Development, 2026)
Wound bed preparation and microbial load control depend on the use of topical antiseptics, requiring a balance between efficacy, biosafety, and economic viability. The objective of this systematic review is to analyze the efficacy, biosafety, and cost-effectiveness of topical antiseptics and novel antimicrobial agents in minimally invasive dermatology. The review followed the PRISMA guidelines and was registered in PROSPERO. A search was conducted in the PubMed database for randomized clinical trials, assessing the risk of bias using the Cochrane RoB 2.0 tool. A supplementary search covered the grey literature for economic data. Advanced formulations, such as polyhexamethylene biguanide (PHMB) and silver nanoparticles (AgNPs), demonstrated clinical superiority and high cellular tolerability in accelerating the healing of complex wounds when compared to traditional therapies. 40% hydrogen peroxide proved to be highly effective and safe for non-invasive removal of seborrheic keratoses. In pharmacoeconomic analysis, modern silver dressings and PHMB generated overall savings by reducing complications, hospital stays, and dressing changes, offsetting the acquisition cost. First-line antifungals maintained high economic efficiency. It is concluded that innovative antiseptic agents offer superior efficacy and biosafety compared to classic antiseptics in dermatology. Their adoption proves cost-effective by optimizing treatment time and improving patient quality of life.